Family, social and cultural determinants of long-lasting insecticidal net (LLIN) use in Madagascar: secondary analysis of three qualitative studies focused on children aged 5-15 years. - Njatosoa, AF; Mattern, C; Pourette, D; Kesteman, T; Rakotomanana, E; Rahaivondrafahitra, B; Andriamananjara, M; Harimanana, A; Razafindrakoto, J; Raboanary, E; Andrianasolo, A; Rogier, C (BioMed Central, 2021)
Background Although it is accepted that long-lasting insecticidal net (LLIN) use is an effective means to prevent malaria, children aged 5 to 15 years do not appear to be sufficiently protected in Madagascar; the malaria prevalence is highest in this age group. The purpose of this research is to summarize recent qualitative studies describing LLIN use among the Malagasy people with a focus on children aged 5–15 years. Methods Qualitative data from three studies on malaria conducted between 2012 and 2016 in 10 districts of Madagascar were analysed. These studies cover all malaria epidemiological profiles and 10 of the 18 existing ethnic groups in Madagascar. A thematic analysis was conducted on the collected data from semi-structured interviews, direct observation data, and informal interviews. Results A total of 192 semi-structured interviews were conducted. LLINs are generally perceived positively because they protect the health and well-being of users. However, regional representations of mosquito nets may contribute to LLIN lower use by children over 5 years of age including the association between married status and LLIN use, which leads to the refusal of unmarried young men to sleep under LLINs; the custom of covering the dead with a mosquito net, which leads to fear of LLIN use; and taboos governing sleeping spaces for siblings of opposite sexes, which leads to LLIN shortages in households. Children under 5 years of age are known to be the most vulnerable age group for acquiring malaria and, therefore, are prioritized for LLIN use when there are limited supplies in households. In contrast, children over 5 years of age, who are perceived to be at less risk for malaria, often sleep without LLINs. Conclusions Perceptions, social practices and regional beliefs regarding LLINs and vulnerability to malaria contribute to the nonuse of LLINs among children over 5 years of age in Madagascar. Modifying LLIN policies to account for these factors may increase LLIN use in this age group and reduce disease burden.